The Influence of Social Media Engagement on Generation Z's Purchase Intention: The Mediating Role of Brand Trust - Reyngga Yusvika Aviandita; Wahyu Febri Ramadhan Sudirman; Ayu Nadhirah (Global Sustainability Research Institute, 2026)
Introduction: The development of social media has transformed marketing strategies, positioning social media engagement as the primary means of building relationships between brands and consumers. However, consumer engagement on social media does not always lead to purchase intention, necessitating an understanding of the role of brand trust as a bridging mechanism for this relationship. This study aims to analyze the influence of social media engagement on brand trust and purchase intention, and to examine the mediating role of brand trust. Methods: This study used a quantitative explanatory approach with a sample of 116 respondents selected through purposive sampling. Data analysis was conducted using SEM-PLS. Instrument testing included convergent and discriminant validity, as well as reliability using Cronbach's Alpha and Composite Reliability. Mediation analysis refers to the Baron and Kenny approach. Results: The results show that social media engagement has a positive and significant effect on brand trust, and brand trust has a positive and significant effect on purchase intention. Mediation testing indicates that brand trust mediates the relationship between social media engagement and purchase intention in certain pathways, although not all mediation pathways are significant. Conclusion and Suggestion: This study concludes that the effectiveness of social media engagement in driving purchase intention is highly dependent on its ability to build brand trust. Future research is recommended to expand the sample, use a longitudinal design, and add other variables to enhance the model's explanatory power.